Age-stratified reference ranges for adenoid hypertrophy in children: a single-center retrospective study - Tao, Enfu; Liang, Wei; Gu, Hongdan; Zhou, Junfen; Zheng, Changhua; Yuan, Junhui (Frontiers in Pediatrics, 2025)
IntroductionAdenoid hypertrophy (AH) is prevalent in 35%–70% of the global pediatric population, leading to airway obstruction and sleep disturbances. Current diagnostic criteria for the adenoid-to-nasopharyngeal (A/N) ratio lack age-specific adjustments, potentially resulting in diagnostic inaccuracies.MethodsThis retrospective study assessed pediatric outpatients aged 1–12 years who underwent lateral nasopharyngeal radiography. Measurements of adenoid depth (AD), nasopharyngeal depth (ND), and A/N ratios were recorded, and age-stratified percentiles (P5-P95) were calculated for four distinct age cohorts. The relationships between AD, ND, and A/N ratios and age were analyzed. Measurements were conducted by two independent radiologists, with any discrepancies adjudicated by a senior expert.ResultsIn this investigation involving 2,629 outpatient children aged between 1 and 12 years, the median AD remained consistent at 14–15 mm, whereas ND increased from 21 to 27 mm, resulting in a decrease in the A/N ratio from 0.68 to 0.56. Pathological hypertrophy was identified in 42% of children aged 1–3 years, compared to 13.7% in those aged 10–12 years, with no significant sex-based differences observed. Age-specific reference ranges showed that both AD and ND increased with age, whereas the A/N ratio decreased. A positive correlation was found between AD and both ND and the A/N ratio, while ND exhibited a negative correlation with the A/N ratio. Significant discrepancies were noted between age-specific A/N ratio percentiles and the current fixed diagnostic criteria for children aged 1–12 years. The study established percentile-based reference values (P5–P95) for AD, ND, and the A/N ratio across four pediatric age groups.ConclusionsThis study established percentile-based reference values (P5–P95) for AD, ND, and the A/N ratio across four pediatric age groups, thereby recommending age-specific diagnostic thresholds for AH in clinical settings.